2006
DOI: 10.1038/ncb1403
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin signatures of pluripotent cell lines

Abstract: Epigenetic genome modifications are thought to be important for specifying the lineage and developmental stage of cells within a multicellular organism. Here, we show that the epigenetic profile of pluripotent embryonic stem cells (ES) is distinct from that of embryonic carcinoma cells, haematopoietic stem cells (HSC) and their differentiated progeny. Silent, lineage-specific genes replicated earlier in pluripotent cells than in tissue-specific stem cells or differentiated cells and had unexpectedly high level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

63
1,118
4
9

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,227 publications
(1,205 citation statements)
references
References 37 publications
63
1,118
4
9
Order By: Relevance
“…Recent studies have documented distinctive properties of nuclear architecture and chromatin structure in stem cells (Azuara et al, 2006;Bernstein et al, 2006;Meshorer and Misteli, 2006). These characteristics of stemness may not be compatible with an effective decatenation checkpoint; in other words, it is possible that stem cells cannot simultaneously maintain multipotency and the decatenation checkpoint.…”
Section: Why a Deficiency In Stem And Progenitor Cells?mentioning
confidence: 99%
“…Recent studies have documented distinctive properties of nuclear architecture and chromatin structure in stem cells (Azuara et al, 2006;Bernstein et al, 2006;Meshorer and Misteli, 2006). These characteristics of stemness may not be compatible with an effective decatenation checkpoint; in other words, it is possible that stem cells cannot simultaneously maintain multipotency and the decatenation checkpoint.…”
Section: Why a Deficiency In Stem And Progenitor Cells?mentioning
confidence: 99%
“…A comprehensive mapping of 18 histone acetylation marks in CD4 + T cells revealed that H3K9ac, H3K18ac, and H3K27ac are mainly located in regions surrounding the transcription start sites (TSS), whereas H4K8ac is elevated in promoter and transcribed regions of active genes [8,9]. Nonetheless, the correlation of intergenic H3K9ac sites with multiple promoter and enhancer marks has been used to infer that H3K9ac can denote active enhancers as well as bivalent promoters in stem cells [10,11]. Moreover, a combination of H3K4me1 and H3K27ac can serve as a readout of active enhancers [1,2,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…This promiscuity may be a result of the epigenetic environment of the ESC genome. Indeed, it has been shown that in these cells the chromatin at promoters of numerous lineage markers, including Sox1, is characterized by histone modifications that are associated both with chromatin accessibility (methylated H3K4) and transcriptional repression (trimethylated H3K27) [53,54]. It is tempting to speculate that these bivalent structures are inherently unstable and that they are dismantled at the beginning of differentiation more rapidly than repressive marks are added at the Pou5f1 locus.…”
Section: Discussionmentioning
confidence: 99%